2021
DOI: 10.17051/ilkonline.2021.01.89
|View full text |Cite
|
Sign up to set email alerts
|

Discovering learning model analysis to improve learning results of social science for elementary school

Abstract: Discovery learning sets the students free to study and learn based on the preferred learning styles, to gain competencies and fulfill the curiosities. Teachers are expected to create circumstance in which students may solve problems by providing the consultation when it is needed. This study aimed to re-analyze the implementation of discovery learning models on improving social studies learning outcomes of students of basic education. This research uses a descriptive approach with meta-analysis method. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The different school condition, different students' proficiencies, different students' health conditions, different implementation of the curriculum will give different impacts on students' learning achievement. Besides, the teachers implementation of the same learning model will have possibly different results [5]. Peneliti mengartikan sebagai berikut "Kondisi sekolah yang berbeda, kemampuan peserta didik yang berbeda, kondisi kesehatan peserta didik yang berbeda, penerapan kurikulum yang berbeda akan memberikan dampak yang berbeda pula terhadap prestasi belajar peserta didik.…”
Section: Hasil Dan Pembahasanunclassified
“…The different school condition, different students' proficiencies, different students' health conditions, different implementation of the curriculum will give different impacts on students' learning achievement. Besides, the teachers implementation of the same learning model will have possibly different results [5]. Peneliti mengartikan sebagai berikut "Kondisi sekolah yang berbeda, kemampuan peserta didik yang berbeda, kondisi kesehatan peserta didik yang berbeda, penerapan kurikulum yang berbeda akan memberikan dampak yang berbeda pula terhadap prestasi belajar peserta didik.…”
Section: Hasil Dan Pembahasanunclassified
“…These models can also be combined with the right media to improve cognitive learning outcomes. The discovery learning model helps students understand a concept actively and independently as well as develop their reasoning in analyzing situations [17], [18]. Described by Khabibah et al [19] that the use of discovery learning-based modules in the learning process is very effective for improving generic science skills.…”
mentioning
confidence: 99%
“…Furthermore, the discovery learning model applied can arouse curiosity by motivating students to continue working until the correct answers are obtained [22]. Setiawati and Sari [18] stated that the discovery learning model could improve learning outcomes. Moreover, Rahman [23] reported that lecturers must design the learning process to develop creative thinking skills in higher education using the YouTube-assisted discovery learning model.…”
mentioning
confidence: 99%